1987
DOI: 10.1038/sc.1987.79
|View full text |Cite
|
Sign up to set email alerts
|

Differences between trunk heat patterns shown by complete and incomplete spinal cord injured veterans

Abstract: SUnlnlaryThermograms showing heat patterns in the trunk of the body were taken of ten intact subjects, seven subjects with incomplete spinal cord injuries (SCI), and fifteen subjects diagnosed as having complete SCIs. Fourteen of the subjects with complete SCIs had a thermal demarcation line across the trunk. This line represented a temper ature gradient of one to 2· 5 degrees Celsius between a relatively warm upper level where sensations were normal and a relatively cool lower level in which sensations were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For example, Uematsu et al indicated that calculation of skin temperature asymmetry (DT sk ) is especially effective in evaluating reported pain [6]. Furthermore, Sherman et al [7] determined difference of temperatures in degrees Celsius between the area with normal sensations and the one with no or abnormal sensations in subjects with complete and incomplete SCI, (1.50 ± 0.62°C and 0.58 ± 0.29°C respectively [7]). Thermography measures the emission of infrared radiation and monitors the temperature distribution of human skin.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Uematsu et al indicated that calculation of skin temperature asymmetry (DT sk ) is especially effective in evaluating reported pain [6]. Furthermore, Sherman et al [7] determined difference of temperatures in degrees Celsius between the area with normal sensations and the one with no or abnormal sensations in subjects with complete and incomplete SCI, (1.50 ± 0.62°C and 0.58 ± 0.29°C respectively [7]). Thermography measures the emission of infrared radiation and monitors the temperature distribution of human skin.…”
Section: Introductionmentioning
confidence: 99%
“…-Rehabilitation medicine, pain detection and location of the neurological level of paralysis in individuals with SCI (92,179,180,188,189,340,342,361,362,463,464);…”
Section:  Traumatologymentioning
confidence: 99%
“…An example of one such study is that of Sherman et al in which skin temperature was compared between an area with normal sensations and an area without sensation or with abnormal sensations in subjects with complete and incomplete SCI. The differences were 1.5±0.62°C and 0.58±0.29°C for the participants with complete and incomplete SCI, respectively (362). Since some nociceptive and most neuropathic pain pathologies are associated with an alteration of the thermal distribution (173), a more recent study on the assessment of pain through IRT proposed statistical computations and distance measures between comparable regions to assess the degree of asymmetry between contralateral ROIs (165).…”
Section: Jones Et Al Indicated That Changes Of a Few Degrees Celsius ...mentioning
confidence: 99%